2015
DOI: 10.1111/sms.12538
|View full text |Cite
|
Sign up to set email alerts
|

Elevated corticospinal excitability in patellar tendinopathy compared with other anterior knee pain or no pain

Abstract: Anterior knee pain (AKP) is a frequent clinical presentation in jumping athletes and may be aggravated by sustained sitting, stair use, and loading of the quadriceps. Corticospinal activation of the quadriceps in athletes with AKP has not yet been investigated, but is important in guiding efficacious treatment. This cross-sectional study assessed corticospinal excitability (CSE) of the quadriceps in jumping athletes using transcranial magnetic stimulation (TMS). Groups consisted of Control (no knee pain); pate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 56 publications
2
44
0
Order By: Relevance
“…Patients enrolled into our study represent non-responders of conservative treatment presenting severe and chronic symptoms. Rio and co-workers recently demonstrated that jumping athletes with PT experience elevated corticospinal excitability for the rectus femoris muscle compared with healthy controls and people with other anterior knee pain, indicating specific pain behavioral neurological alterations in PT patients [ 47 ]. We assumed, that a longer duration of symptoms would (especially in our study population) lead to inferior outcome measures as recently published.…”
Section: Discussionmentioning
confidence: 99%
“…Patients enrolled into our study represent non-responders of conservative treatment presenting severe and chronic symptoms. Rio and co-workers recently demonstrated that jumping athletes with PT experience elevated corticospinal excitability for the rectus femoris muscle compared with healthy controls and people with other anterior knee pain, indicating specific pain behavioral neurological alterations in PT patients [ 47 ]. We assumed, that a longer duration of symptoms would (especially in our study population) lead to inferior outcome measures as recently published.…”
Section: Discussionmentioning
confidence: 99%
“…65 However, our review did not find compelling evidence of M1 disinhibition when people with and without pain were compared. This discrepancy is likely because of our inclusion of more recent studies 7,11,52,53,60,66,72,79,85,93,94 and exclusion of studies containing neurological populations. 45 Also, CRPS studies were separated from neuropathic pain in our subgroup analyses because they have different diagnostic criteria and pathophysiology.…”
Section: Evidence Of Altered Corticospinal Excitability In Chronic Painmentioning
confidence: 99%
“…Five studies investigated 2 or more chronic pain conditions. 11,72,73,75,82 Participant sex (n = 4 studies) and age (n = 3 studies), pain intensity (n = 22 studies), and the duration of the pain (n = 7 studies) were not reported by some of the included studies. The characteristics of included studies are summarized in Tables 2 and 3.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…This study interestingly did not find changes in gastrocnemius muscle stiffness following isometric training but only following plyometric training. Considering isometric training has been used as a key treatment for Achilles tendinopathy,29 this may be only targeting Achilles tendon rehabilitation and not gastrocnemius muscle rehabilitation. It should also be considered that the significant differences observed in the gastrocnemius stiffness between the tendinopathic and control groups in our study may be in relation to corticospinal excitability as suggested in patients with patellar tendinopathy 30.…”
Section: Discussionmentioning
confidence: 99%